2011
DOI: 10.1038/ncomms1559
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 mediates spinal antinociception induced by acetaminophen and the cannabinoid Δ9-tetrahydrocannabiorcol

Abstract: TRPA1 is a unique sensor of noxious stimuli and, hence, a potential drug target for analgesics. Here we show that the antinociceptive effects of spinal and systemic administration of acetaminophen (paracetamol) are lost in Trpa1 − / − mice. The electrophilic metabolites N-acetylp-benzoquinoneimine and p-benzoquinone, but not acetaminophen itself, activate mouse and human TRPA1. These metabolites also activate native TRPA1 and, as a consequence, reduce voltage-gated calcium and sodium currents in primary sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
261
3
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(271 citation statements)
references
References 51 publications
2
261
3
5
Order By: Relevance
“…The results of some previous work indicate that the mechanisms behind its pain killing effect may be distinct from the antipyretic mechanism described in the present study. In a model of tonic pain in rats, Bonnefont and collaborators (2007) showed an involvement of 5-HT 1A receptordependent mechanisms in acetaminophen-produced antinociception, and quite recently, Andersson et al (2011) demonstrated that acetaminophen, via its metabolites p-benzoquinone and N-acetyl-p-benzoquinoneimine, produces antinociception through the activation of the TRPA1 receptor on the central nerve endings of spinal nociceptive fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of some previous work indicate that the mechanisms behind its pain killing effect may be distinct from the antipyretic mechanism described in the present study. In a model of tonic pain in rats, Bonnefont and collaborators (2007) showed an involvement of 5-HT 1A receptordependent mechanisms in acetaminophen-produced antinociception, and quite recently, Andersson et al (2011) demonstrated that acetaminophen, via its metabolites p-benzoquinone and N-acetyl-p-benzoquinoneimine, produces antinociception through the activation of the TRPA1 receptor on the central nerve endings of spinal nociceptive fibers.…”
Section: Discussionmentioning
confidence: 99%
“…4 acetaminophen has been suggested to reduce the oxidative stress (Maharaj et al, 2006;Tripathy and Grammas, 2009) that has been implicated in prostaglandin release and fever (Hou et al, 2011;Riedel et al, 2003). Finally, there is evidence that the analgesic effect of acetaminophen may be ascribed to its metabolites, through the activation of endogenous receptor systems, such as the 5-hydroxytryptamine and endocannabinoid systems (Andersson et al, 2011;Bonnefont et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several other concepts of the mechanism of action of paracetamol have been forwarded, including the involvement of the opioid [13, [65][66][67][68], adrenergic [69][70][71] and cholinergic [72,73] systems and that of nitric oxide synthetase [74][75][76][77], adenosine receptors [48,78,79] and calcium channel TRPA1 [80]. However, other studies have yielded conflicting findings notably concerning the opioid [40,81,82], adrenergic [37,71,83] and cholinergic [84] systems.…”
Section: Resultsmentioning
confidence: 99%
“…We now know more about paracetamol's mechanisms of analgesia: Paracetamol is a pro-drug whose active metabolites have effects on both TRPV1 and TRPA1 receptors and on the cannabinoid system (Högestätt et al, 2005;Andersson et al, 2011). These effects appear to increase significantly the risk of neuro-developmental problems and attention deficit/ hyperactivity disorder of young children exposed to paracetamol in utero (Brandlistuen et al, 2013;Liew et al, 2014).…”
mentioning
confidence: 99%